The Implementation of Accelerated Learning Model Assisted By Autograph on Students' Adaptive Reasoning Ability and Environmental Literacy - Amirah, Izzatul; Anggoro, Bambang Sri; Gunawan, Wawan (CV FOUNDAE, 2023)
This research aimed to assess the impact of implementing the Accelerated Learning model on the adaptive reasoning ability and environmental literacy of students. Employing a quantitative research approach, the study utilized a quasi-experimental post-test only control group design. A total of 180 eighth-grade students from UPT SMP Negeri 3 Bandar Lampung constituted the participants in this study, and a sample of 90 students was chosen using cluster random sampling. The analytical process involved conducting normality and homogeneity tests, and the research hypothesis was assessed using Multivariate Analysis of Variance (MANOVA). The results of the MANOVA test revealed a significance level of 0.000, underscoring a substantial impact of Accelerated Learning assisted by Autograph media on both the adaptive reasoning ability and environmental literacy of students. As such, the study concludes that the integration of the Accelerated Learning model with Autograph media proves effective for enhancing the overall learning process.